"Sometimes I don't have a pulse … and I'm still alive!" Interviews with healthcare professionals to explore their experiences of and views on population-based digital health technologies. (May 2021) - Tomasella, Flavio; Morgan, Heather May
Background: Digital technologies are increasingly becoming an integral part of our daily routine and professional lives, and the healthcare field is no exception. Commercially available digital health technologies (DHTs – e.g. smartphones, smartwatches and apps) may hold significant potential in healthcare upon successful and constructive implementation. Literature on the topic is split between enthusiasm associated with potential benefits and concerns around privacy, reliability and overall effectiveness. However, little is known about what healthcare professionals (HCPs) have experienced so far with patients and what they perceive as the main advantages and disadvantages of adoption. This study therefore aims to investigate current perceptions of HCPs towards self-tracked health-related outputs from devices and apps available to the public. Methods: Nine HCPs volunteered to take part in semi-structured interviews. Related data were thematically analysed, following a deductive approach with the construction of a framework based on expected themes from the relevant literature, and themes identified from the first two interviews. Findings: The following main themes in relation to DHTs were identified and explored in detail: HCPs' experience, knowledge and views; advantages and disadvantages; barriers towards healthcare implementation and potential solutions; future directions. While most participants were adopters of DHTs and held positive views about them, their overall experience with patients and the technology was limited. Potential reasons for this were explored, including factors such as time/resources; colleagues' mindset; lack of evidence of effectiveness for practice; data security concerns. Conclusions: The potential advantages of DHTs' adoption in healthcare are substantial, e.g. patient autonomy, time/resources saving, health and behaviour change promotion, but are presently premature. Therefore, future research is warranted, focussing on addressing barriers, minimising disadvantages, and assessing the clinical value of commercially available DHTs.